2019
DOI: 10.1002/aqc.3239
|View full text |Cite
|
Sign up to set email alerts
|

Decimation of a population of the endangered species Scutellastra mexicana (Broderip and Sowerby, 1829) (Mollusca, Gastropoda) in the Marías Island (Eastern Ocean Pacific) Biosphere Reserve

Abstract: Scutellastra mexicana is the largest known patellid limpet species and probably is one of the most endangered marine invertebrates. The species was once distributed along the American Pacific coast from Mexico to Peru, but their large size (up to 35 cm long) and easy accessibility (shallow sublittoral), made it very vulnerable to human collection and now is extinct on most of the mainland Mexican coast. In August 2017, a large population of this species was found on María Cleofas island, off the coast of west‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 15 publications
3
17
0
Order By: Relevance
“…Currently, the exploitation of limpets continues for either ornamental, food, or fishing bait collection purposes (Espinosa and Rivera-Ingraham, 2017;Firth, 2021). The exploited taxa include the genera Cellana (Lasiak, 1993;Harada et al, 1997;McCoy, 2008), Cymbula (Branch and Odendaal, 2003), Lottia (Pombo and Escofet, 1996;Sagarin et al, 2007), Patella (Guerra-Garcıá et al, 2004;Guallart et al, 2013c;Henriques et al, 2017;Sousa et al, 2019a;Sousa et al, 2020a), and Scutellastra (Carballo et al, 2020;Valdez-Cibriań et al, 2021). Overfishing has led to a detrimental impact on several populations of limpets worldwide, resulting in smaller specimens and population sizes, a reduced female:male ratio, and an overall plummet of biomass and reproductive/recruitment output (Branch, 1975;Branch and Odendaal, 2003;Guerra-Garcıá et al, 2004;Espinosa et al, 2006;Espinosa et al, 2009a;Sousa et al, 2019b;Sousa et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the exploitation of limpets continues for either ornamental, food, or fishing bait collection purposes (Espinosa and Rivera-Ingraham, 2017;Firth, 2021). The exploited taxa include the genera Cellana (Lasiak, 1993;Harada et al, 1997;McCoy, 2008), Cymbula (Branch and Odendaal, 2003), Lottia (Pombo and Escofet, 1996;Sagarin et al, 2007), Patella (Guerra-Garcıá et al, 2004;Guallart et al, 2013c;Henriques et al, 2017;Sousa et al, 2019a;Sousa et al, 2020a), and Scutellastra (Carballo et al, 2020;Valdez-Cibriań et al, 2021). Overfishing has led to a detrimental impact on several populations of limpets worldwide, resulting in smaller specimens and population sizes, a reduced female:male ratio, and an overall plummet of biomass and reproductive/recruitment output (Branch, 1975;Branch and Odendaal, 2003;Guerra-Garcıá et al, 2004;Espinosa et al, 2006;Espinosa et al, 2009a;Sousa et al, 2019b;Sousa et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the size of the limpets ranged from 5.0 to 23.3 cm in length compared to the maximum size for Scutellastra mexicana of 35.0 cm (Powell, 1973). Carballo et al (2020) reported a maximum size of 26.0 cm for limpets in the Islas Marias. Whilst the maximum length recorded in this study was lower than those mentioned above it was considerably greater than that reported by Ávalos‐Vizcaino & Méndez‐Reyes (1992) in Michoacan (14.6 cm for females and 15.6 cm for males) after years of intense exploitation of the species.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Carballo et al (2020) determined a density of 0.7 limpets/m 2 on a site in the Islas Marias archipelago. This is a remote place and a natural protected area, so it is likely to be an unexploited site as well as the last relict for this species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations